Explanation :
16) 5a( -3b)(-2a²b³)
[tex] = \tt \: 5a( - 3b)( - 2 {a}^{2} {b}^{3} ) \: \: \: \: \: \: \: \: \: \\ = \tt \: 5a[( - 3b) \times ( - 2 {a}^{2} {b}^{3} )] \\ \tt = 5a \times 6 {a}^{2} {b}^{4 } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ = \tt \: 30 {a}^{3} {b}^{4 } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \\ \\ [/tex]
17) 11 (4cd)( -cd⁵)
[tex] = \tt \: 11 (4cd)( -cd⁵) \: \: \: \: \: \: \: \: \: \\ = \tt \: 11[( 4cd) \times ( - cd{}^{5} ) ] \\ \tt = 11 \times ( - 4 {c}^{2} {d}^{6 }) \: \: \: \: \: \: \: \: \: \\ \tt \: = - 44{c}^{2} {d}^{6 } \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \\ \\ [/tex]
18) ( -xy³)(4x²y)
[tex] \tt \: = ( -xy³)(4x²y) \\ \tt \: = - 4{x}^{3} {y}^{4} \: \: \: \: \: \: \\ \\ \\ \\ [/tex]
22) (7a)(3ab) - 4a²b
[tex] \tt =(7a)(3ab) - 4a²b \\ \tt \: = 21 {a}^{2} b - 4 {a}^{2} b \\ \tt \: = 17 {a}^{2} b \: \: \: \: \: \: \: \: \: \\ \\ \\ \\ [/tex]
23) (2y²)(4xy³) + (3xy⁴)(5y)
[tex] \tt =(2y²)(4xy³) + (3xy⁴)(5y) \\ \tt = 8 x{y}^{5} + 15x {y}^{5} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \tt = 23x {y}^{5} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \\ \\ [/tex]